Peran Unit Patroli Satuan Sabhara Dalam Mencegah Tindak Pidana Pencurian Dan Pemberatan Di Polres Ciamis - Mahendra, Pande Putu Yoga (Indonesian Journal of Police Studies, 2019)
This study aims to describe the role of the Sabhara Unit patrol unit, the factors that influence the Role of the Sabhara Unit Patrol Unit, and the Role performed by Sat Sabhara in preventing criminal acts of theft and weighting at the Ciamis Police Station. The study was conducted using a qualitative approach in the form of written or oral words from people and observable behavior. Data collection techniques used were interviews, observation and document study. The results of this study indicate that the managerial role of the Ciamis Police Sabhara Unit patrol unit has been carried out well. The factors that influence the implementation of the role of the patrol unit in preventing theft by weighting at the Ciamis Police Station are internal and external as well as the role carried out by the Sat Sabhara Ciamis Police Station is with primary prevention, secondary prevention and tertiary prevention. Based on the results of the research above, it can be concluded that the role of the Sat Sabhara Ciamis Regional Police patrol unit has not been able to completely prevent criminal acts of theft by weighting. The advice given is to provide a reward and punishment system to Sat Sabhara members, provide training and vocational education to patrol members, and conduct an analysis and evaluation of the patrol program that has been made.